Vitrectomy for idiopathic macular hole - Parravano, Mariacristina (Cochrane Database Syst Rev, 2015)
BACKGROUND: A macular hole is an anatomic opening in the retina that develops at the fovea. Macular holes can be seen in highly myopic eyes or following ocular trauma, but the great majority are idiopathic. Pars plana vitrectomy was introduced to treat full‐thickness macular holes, which if left untreated have a poor prognosis since spontaneous closure and visual recovery are rare. Vitrectomy is a surgical technique involving the removal of the vitreous body that fills the eye. The surgeon inserts thin cannulas into the eyes through scleral incisions to relieve traction exerted by the vitreous or epiretinal membranes to the central retina and to induce glial tissue to bridge and close the hole. OBJECTIVES: The primary objective of this review was to examine the effects of vitrectomy for idiopathic macular hole on visual acuity. A secondary objective was to investigate anatomic effects on hole closure and other dimensions of visual function, as well as to report on adverse effects recorded in included studies. SEARCH METHODS: We searched the Cochrane Eyes and Vision Group Trials Register (4 March 2015), the Cochrane Central Register of Controlled Trials (CENTRAL; 2015, Issue 2), Ovid MEDLINE, Ovid MEDLINE In‐Process and Other Non‐Indexed Citations, Ovid MEDLINE Daily, Ovid OLDMEDLINE (January 1946 to March 2015), EMBASE (January 1980 to March 2015), Latin American and Caribbean Health Sciences Literature Database (LILACS) (January 1982 to March 2015), the Web of Science Conference Proceedings Citation Index‐Science (CPCI‐S) (January 1980 to March 2015), the ISRCTN registry (www.isrctn.com/editAdvancedSearch), ClinicalTrials.gov (www.clinicaltrials.gov) and the World Health Organization (WHO) International Clinical Trials Registry Platform (ICTRP) (www.who.int/ictrp/search/en). We did not use any date or language restrictions in the electronic searches for trials. We last searched the electronic databases on 4 March 2015. SELECTION CRITERIA: We included randomised controlled trials comparing vitrectomy (with or without internal limiting membrane peeling) to no treatment (that is observation) for macular holes. DATA COLLECTION AND ANALYSIS: We used standard methodological procedures expected by Cochrane. Two review authors independently extracted the data. We estimated best corrected visual acuity and macular hole closure at 6 to 12 months of follow‐up. MAIN RESULTS: Three studies provided data on the comparison between vitrectomy and observation in eyes with macular hole and visual acuity less than 20/50. Two studies, conducted in the USA and published in 1996 and 1997, used a similar protocol and included participants with stage II macular hole (42 eyes randomised, 36 analysed, number of participants not reported) or participants with stage III/IV hole (129 eyes of 120 participants, 115 eyes in analyses). The third study, conducted in the UK and published in 2004, included 185 eyes of 174 participants with full‐thickness macular hole (41 eyes with stage II holes and 74 eyes with stage III/IV holes in analyses). Studies were of good quality for randomisation and allocation concealment, whereas visual acuity measurement was unmasked. At 6 to 12 months, visual acuity was improved by about 1.5 Snellen lines (‐0.16 logMAR, 95% confidence intervals ‐0.23 to ‐0.09 logMAR, 270 eyes, moderate‐quality evidence). The chances of macular hole closure at 6 to 12 months were greatly increased using vitrectomy, yielding an odds ratio of 31.4 (95% confidence intervals 14.9 to 66.3, 265 eyes, high‐quality evidence; raw sum data: 76% vitrectomy, 11% observation). Vitrectomy was beneficial both in smaller (stage II) and in larger (stage III/IV) macular holes. The largest study reported that cataract surgery was needed in about half of cases at two years after operation and that retinal detachment occurred in about 5% of operated eyes. AUTHORS' CONCLUSIONS: Vitrectomy is effective in improving visual acuity, resulting in a moderate visual gain, and in achieving hole closure in people with macular hole. However, these results may not apply to modern surgery due to technological improvements in vitrectomy techniques.